Ensaios sobre a estrutura a termo da taxa de juros - Glasman, Daniela Kubudi (2013)
This thesis consists of three works that analyses the term structure of interest rates using different datasets and models. Chapter 1 proposes a parametric interest rate model that allows for segmentation and local shocks in the term structure. Adopting U.S. Treasury data, two versions of this segmented model are implemented. Based on a sequence of 142 forecasting experiments, the proposed models are compared to established benchrnarks and find that they outperform in out-of-sample forecasting results, specially for short-term maturities and for the 12-month horizon forecast. Chapter 2 adds no-arbitrage restrictions when estimating a dynamic gaussian polynomial term structure model for the Brazilian interest rate market. This article propose an important approximation of the time series of term structure risk factors, that allows to extract the risk premium embedded in interest rate zero coupon instruments without having to run a fui! optimization of a dynamic model. This methodology has the advantage to be easily implemented and provides a good approximation for the term structure risk premia that can be used in many applications. Chapter 3 models the joint dynamic of nominal and real yields using an affine macro-finance no-arbitrage term structure model in order to decompose the break even inflation rates into inflation risk premiums and inflation expectations in the US market. The Yields-Only and the Macro version of this model are implemented and the estimated inflation risk premiums obtained are small and quite stable during the sample period, but have differences when comparing the two versions of the model.